Polymer Characterization by Combined Chromatography-Infrared Spectroscopy. (18th December 2011) - Dwyer, James L.; Zhou, Ming
Abstract : Infrared spectroscopy is widely used in the analysis and characterization of polymers. Polymer products are not a singular species, but rather, they are a population of polymer molecules varying in composition and configuration plus other added components. This paper describes instrumentation that provides the benefit or resolving polymer populations into discrete identifiable entities, by combining chromatographic separation with continuous spectra acquisition. The technology also provides a way to determine the mass distribution of discrete components across the chromatographic distribution of a sample. Various examples of application of this technology to polymer products are described. Examples include additives analysis, resolution of polymer blends, composition characterization of copolymers, analysis of degradation byproducts, and techniques of analysis of reactive polymer systems.